Effect of clap-and-fling mechanism on force generation in flapping wing micro aerial vehicles. (27th February 2019) - Jadhav, S S; Lua, K B; Tay, W B
Abstract: The clap-and-fling effect, first observed in a number of insects, serves as a lift-enhancing mechanism for bio-inspired flapping wing micro aerial vehicles (MAV). In our comprehensive literature survey, we observe that the effect manifests differently in insects and contemporary MAVs; insects have active control over the angle of attack and stroke plane of the wing, whereas a number of kinematic parameters of an MAV's flexible wings are determined passively. Although there is consensus that flinging motion significantly enhances aerodynamic lift, the effect of clapping motion is not well-studied. To address this gap, we experimentally quantify the contribution of clapping motion using force measurement and particle image velocimetry. No significant enhancement in lift was observed due to clapping motion, because the momentum jet was too weak. However, the kinematics and flow conditions in our study were notably different from those in the previous studies on insect models. The wings of the MAV are flexible, and deform passively. Hence, the clapping of the trailing edges, and the appearance of a trailing edge momentum jet, was delayed and significantly suppressed. Using force measurement and CFD simulations, it was also found that the lesser the distance between the leading edges of the wings at the end of clap, the higher is the lift due to the subsequent fling.